Distribution of OFDM radio signals over optical fiber - Andrade, Paulo (2011)
In this paper, we will study, via simulation, several transmission schemes of OFDM radio signals over optical fiber, in order to evaluate their main advantages and limitations. We will start by studying the transmission of 2 OFDM channels at 8GHz and 60 GHz, considering several types of optical modulation: Double Sideband (DSB), Vestigial Sideband (VSB) and Double Sideband-Carrier Suppressed (DSB-CS). Then, we will proceed to assess the transmission of few OFDM channels, generated according to the standards MB-OFDM UWB (ECMA-368) and 60GHz WPAN (ECMA-387).